Admission Features Associated With Paroxysmal Sympathetic Hyperactivity After Traumatic Brain Injury: A Case-Control Study. Issue 10 (29th April 2021) - Podell, Jamie E.; Miller, Serenity S.; Jaffa, Matthew N.; Pajoumand, Mehrnaz; Armahizer, Michael; Chen, Huanwen; Tripathi, Hemantkumar; Schwartzbauer, Gary T.; Chang, Wan-Tsu W.; Parikh, Gunjan Y.; Hu, Peter; Badjatia, Neeraj
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Paroxysmal sympathetic hyperactivity occurs in a subset of critically ill traumatic brain injury patients and has been associated with worse outcomes after traumatic brain injury. The goal of this study was to identify admission risk factors for the development of paroxysmal sympathetic hyperactivity in traumatic brain injury patients. DESIGN: Retrospective case-control study of age- and Glasgow Coma Scale–matched traumatic brain injury patients. SETTING: Neurotrauma ICU at the R. Adams Cowley Shock Trauma Center of the University of Maryland Medical System, January 2016 to July 2018. PATIENTS: Critically ill adult traumatic brain injury patients who underwent inpatient monitoring for at least 14 days were included. Cases were identified based on treatment for paroxysmal sympathetic hyperactivity with institutional first-line therapies and were confirmed by retrospective tabulation of established paroxysmal sympathetic hyperactivity diagnostic and severity criteria. Cases were matched 1:1 by age and Glasgow Coma Scale to nonparoxysmal sympathetic hyperactivity traumatic brain injury controls, yielding 77 patients in each group. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Admission characteristics independently predictive of paroxysmal sympathetic hyperactivity included male sex, higher admission systolic blood pressure, and initial CT evidence of diffuse axonal injury, intraventricular hemorrhage/subarachnoid hemorrhage, complete cisternal effacement, and absence of contusion. Paroxysmal sympathetic hyperactivity cases demonstrated significantly worse neurologic outcomes upon hospital discharge despite being matched for injury severity at admission. CONCLUSIONS: Several anatomical, epidemiologic, and physiologic risk factors for clinically relevant paroxysmal sympathetic hyperactivity can be identified on ICU admission. These features help characterize paroxysmal sympathetic hyperactivity as a clinical-pathophysiologic phenotype associated with worse outcomes after traumatic brain injury.